ŚRODKI OCHRONY ŚWIADKA - Kałdon, Barbara (Zeszyty Prawnicze, 2017)
Means of the protection of the witness Summary Anonymous and key witness are involved undoubtedly in young and controversial institutions. Their opponents accuse them of breaking trial and constitutional principles. Sceptics regard useless, unnecessary and ineffective them. However defenders of these institutions claim that the life and the health of the witness as well as the fight against the organized crime should be more important than answers in a model fashion accepted. According to keen supporters they can it to be effective measures to the fight against most dangerous crime.